Формирование способности к самостоятельной познавательной деятельности и умению учиться на протяжении всей жизни - Сельханова, Ж. Н. (My University, 2016)
The competence approach is one of the directions for education renewal in the strategy of modernization of General education in Kazakhstan. All these qualities can successfully build using the competence approach in the teaching of mathematics, which is one of personal and social meanings of education
Keywords: Competence; mathematical competence; independence; functional literacy